Factors associated with the utilisation of postnatal care services among the mothers of Nepal: analysis of Nepal Demographic and Health Survey 2011 - Khanal, Vishnu; Adhikari, M.; Karkee, R.; Gavidia, Tania (Biomed Central Ltd., 2014)
Background: Postnatal care is essential to save the life of the mother and newborn. Knowledge on the determinants of postnatal care assists the policy makers to design, justify and implement appropriate interventions. The current study aimed to analyse the factors associated with utilisation of postnatal care services by mothers in Nepal based on the data from Nepal Demographic and Health Survey (NDHS) 2011. Methods: This study utilised the data from NDHS 2011. The association between utilisation of at least one postnatal care visit (within 6 weeks of delivery) and immediate postnatal care (within 24 hours of delivery) with selected factors was examined by using Chi-square test (?2), followed by multiple logistic regression.Result: Of the 4079 mothers, 43.2% reported attending postnatal care within the first six weeks of birth, while 40.9% reported attending immediate postnatal care. Mothers who were from urban areas, from rich families, who were educated, whose partners were educated, who delivered in a health facility, who had attended a four or more antenatal visits, and whose delivery was attended by a skilled attendant were more likely to report attending at least one postnatal care visit. On the other hand, mothers who reported agricultural occupation, and whose partners performed agricultural occupation were less likely to have attended at least one postnatal care visit. Similarly, mothers who were from the urban areas, from rich families, who were educated, whose partners were educated, who had attended four or more antenatal visits, who delivered in a health facility and had delivered in the presence of a skilled birth attendant were more likely to report attending immediate postnatal care. Mothers who reported agricultural occupation, and whose partners performed agricultural occupation were less likely to attend immediate postnatal care. Conclusion: The majority of postnatal mothers in Nepal did not seek postnatal care. Increasing utilisation of the recommended four or more antenatal visits, delivery at health facility and increasing awareness and access to services through community-based programs especially for the rural, poor, and less educated mothers may increase postnatal care attendance in Nepal.